O kilku typach innowacji frazeologicznych w powieści McDusia Małgorzaty Musierowicz - Miękus, Paulina Anna (Poznańskie Spotkania Językoznawcze, 2015)
The aim of this thesis is the analysis and interpretation of selected phraseological innovations in the Małgorzata Musierowicz’s novel McDusia. The author elaborates on extended supplementary innovation and mixed paraphrasing and innovation of collocations, which are combined into two idioms. Analysis and interpretation of the selected types of phraseological innovations in the Małgorzata Musierowicz’s novel McDusia lead to the following conclusion: both are justified in terms of situation. The purpose of phraseological innovations is to make narration more expressive and stress the anthropocentric point of view. Phraseological innovations individualize the characters’ utterances and make featured situations more imaginable. Their role is stylisation, what means that the most often they recall paterns of Polish colloquial language not including swear words.